Cosmic Background Measurements at a Proposed Underground Laboratory by the REGARD Muontomograph. Issue 1 (January 2016) - Oláh, L; Surányi, G; Barnaföldi, G G; Bemmerer, D; Hamar, G; Melegh, H G; Varga, D
Abstract: A portable cosmic particle tracking detector has been developed by the REGARD group with angular resolution of 10 mrad. The Close Cathode Chamber-based tracking system is optimized for environmental and geophysical applications with its weight of 15 kg and size of 51 cm × 43 cm × 32 cm. Our aim was to determine the cosmic background at the site of the proposed accelerator and experimental facilities at an approximate 50 meter depth in Felsenkeller, Dresden, Germany. Here, we present our high-precision muon flux measurements, which have been performed during 44 days in one of the tunnels. Angular acceptance of our mapping covered full 2π solid angle of the upper hemisphere. The maximum flux value is found to be below 2.5 m -2 sr -1 s -1 .